Antifungal and Antioxidant Activity of Psoralea corylifolia L. Seeds : An Ethnomedicinal Plant - Kiran, B.; Lalitha, V. (Challenges and Advances in Pharmaceutical Research Vol. 8, 2022)
Medicinal plants are the local heritage with global importance and world is endowed with a rich wealth of medicinal plants. Plants have a great potential to be effective against the growth of pathogenic fungi. The Psoralea corylifolia is commonly known as babchi or bakuchi, used to cure psoriasis, leprosy, leucoderma, diabetes, indigestion, constipation, cardiac failure, coughs, asthma and osteoporosis. The aim of this study was to evaluate the In vitro antifungal activity of aqueous and solvent extracts of seeds of P. corylifolia against five seed borne fungi of maize viz., Curvularia lunata, Dreschslera halodes, Alternaria alternata, Cladosporium cladosporioides and Rhizopus sp. In aqueous extract, maximum inhibition was observed in A. alternata and recorded 95.4% of inhibition at 50% concentration followed by C. lunata (86.0%), Rhizopus sp.(82.3%), D. halodes (68.0%) and C. cladosporioides (57.7%). Significant activity was observed at 10, 20, 30 and 40% concentration. When solvent extracts were evaluated at concentrations of 250, 500, 750, and 1000\(μ\)l, petroleum ether extract showed the greatest degree of inhibition while methanol extract showed the least amount of activity. At the prescribed 2% dose, full inhibition was seen against all of the test fungi examined when compared to the synthetic fungicides Bavistin and Thiram. Superoxide scavenging activity was much above the standards. Thus the results of the present investigation clearly reveals that the petroleum ether extract has very high antioxidant activity suggesting that the extract could be exploited to prevent quality loss of foods during storage.